STUDY ON THE MANUFACTURE OF PLYWOOD FROM EUCALYPTUS CAMALDULENSIS DEHNH. - Promachotikool, Montree; Ounjittichai, Chaiyaporn (วารสารวนศาสตร์ไทย, 2022)
Verifications of plywood manufacture from Eucalyptus camaldulensis Dehnh. were performed both interior and exterior plywood panels. Preheating of the bolt at 80 ° C for 6 hours produced interior plywood samples with 28.89 kg./cm.2 wet shear test and 64% wood failure. The preheating high temperature (80 ° C) caused peeling problem by expanding free splitting of log ends on cross cutting. Nevertheless, the preheating at 70 ° C could slightly prevent the area of free split expanding and preheating in sodium hydroxide solution (pH 11 12) could increase the aveneer yield. The bolts could be peeled after it had been warmed in the solution for 6 hours. Wet test gluability of interior plywood combination between Eucalyptus and Para rubber wood had low wood failure (15%) but the interior plywood combination from Eucalyptus and Dipterocarpus sp. showed 41% wood failure. Investigations of exterior plywood from the bolts preheated at 70 ° C for 24, 48, 78 hr., 80 ° C for 6, 12 hr. and warmed in sodium hydroxide solution (pH 11-12) at 70 ° C for 6, 12, 24 hr. brought about 5-31% wood failures, 20-28 kg./cm.2 dry shear strengths and showed the shear strengths between 10-23 kg./cm.2, 10-41% wood filtures after cyclic boil test for 72 hours. The plywood panels made from Eucalyptus-para rubber combination had dry shear strength 30.14 kg./cm.2, 54% wood failure and provided 17.60 kg./cm.2 shear strength, 35% wood failure after cyclic boil test. Moreover, the exterior plywood combination from Eucalyptus and Dipterocarpus sp. produced 34.55 kg./cm.2 dry shear strength, 64% wood failure and showed 24.61 kg./cm.2 shear strength, 60% wood failure after cyclic boil test.